Hypercholesterolemia-induced oxidative stress & its link to age related diseases - (:unkn) unknown (Turkiye Klinikleri, 2009)
Free radicals and oxidants, cause potential danger for cellular molecules during the lifetime. Oxidative stress is the imbalance between free radical formation and antioxidant defense towards free radicals. Oxidative stress plays role in aging and pathogenesis of several diseases. In this process, age related diseases such as Alzheimer and atherosclerosis are crucial. Since protein mechanisms play important role in these diseases, protein oxidation parameters are preferred as indicator of oxidative stress. Protein aggregates as advanced protein oxidation products especially accumulate with aging are widespread used in studies and investigation of their production and determination of these products are thought to bring benefit for the prevention and treatment of the diseases. Copyright © 2009 by Türkiye Klinikleri.
Keywords: Aging; Disease; Oxidative stress; Protein oxidation